Fire Safety of Timber Buildings – The Case of Photovoltaic Systems - Nik Rus; Andrea Lucherini; Grunde Jomaas; Mohammad Derikvand (BioResources)
Photovoltaic (PV) systems play an important role in reducing society’s dependence on carbon-based energy sources, and their coupling with timber buildings is an interesting and expected solution for meeting sustainability requirements in the modern built environment. However, both PV systems and timber structures have unique fire safety challenges, and their combination may introduce additional risks. Therefore, relevant fire hazards associated with each of the technologies and their pairing are discussed. The findings highlight the importance of revising fire testing standards and developing tailored safety measures to identify and manage these risks.